"A Finer Type of Radio": The Women's National Radio Committee and Its Battles for Better Radio Programming. Issue 2 (3rd April 2019) - Proffitt, Jennifer M.
Abstract : This manuscript examines the efficacy of the Women's National Radio Committee (WNRC) and its influence on the radio industry in the mid-1930s. For the WNRC, giving awards to model programming was more effective to encourage change than merely complaining. As such, one of its most significant contributions was its annual radio awards ceremonies. The WNRC also attempted to distance itself from the caricatures of clubwomen and reformers to make the group more acceptable to radiomen. Once the WNRC asserted its influence in a way that industry executives could not control, they attempted—with some success—to contain the group's power.